Dicer- and Bulge Stem Cell-Dependent MicroRNAs During Induced Anagen Hair Follicle Development - Vishlaghi, Neda; Lisse, Thomas S. (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs (miRNAs) are a major class of conserved non-coding RNAs that have a wide range of functions during development and disease. Biogenesis of canonical miRNAs depend on the cytoplasmic processing of pre-miRNAs to mature miRNAs by the Dicer endoribonuclease. Once mature miRNAs are generated, the miRNA-induced silencing complex, or miRISC, incorporates one strand of miRNAs as a template for recognizing complementary target messenger RNAs (mRNAs) to dictate post-transcriptional gene expression. Besides regulating miRNA biogenesis, Dicer is also part of miRISC to assist in activation of the complex. Dicer associates with other regulatory miRISC co-factors such as trans-activation responsive RNA-binding protein (Tarbp2) to regulate miRNA-based RNA interference. Although the functional role of miRNAs within epidermal keratinocytes have been extensively studied within embryonic and post-natal mouse skin, its contribution to the normal function of hair follicle bulge stem cells (BSCs) during post-natal hair follicle development is unknown. With this question in mind, we sought to ascertain whether Dicer-Tarpb2 plays a functional role within BSCs during induced anagen development by utilizing conditional knockout mouse models. Our findings suggest that Dicer, but not Tarbp2, functions within BSCs to regulate induced anagen (growth) development of post-natal hair follicles. These findings strengthen our understanding of miRNA-dependency within hair follicle cells to define a boundary for post-transcriptional gene regulation during anagen development.